The Influence Of Profitability, Company Size, Media Exposure, And Leverage On Carbon Emissions Disclosure - Aldita Diva Syahdanti; Fenny Marietza (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The purpose of the study is to ascertain the influence of profitability, company size, media exposure and leverage on carbon emission disclosure. Previous research, carbon emission disclosures have not been consistent, so it is worth testing again. The novelty of the study, added the factor of media exposure. Measurement of carbon emission disclosure using information disclosure index based on CDP. The research method uses multiple linear regression. Data was collected from 37 companies in the agriculture and mining sectors in the 2019-2022 annual report. In this case, Return on Assets (ROA), Total Assets Value and high media exposure affect the disclosure of carbon emissions. Meanwhile, a high Debt to Assets Ratio (DAR) has no influence on carbon emission disclosure. The findings show agricultural and mining companies that disclose carbon emissions are affected by high profitability, large company size, and high media exposure. Companies that use leverage, meanwhile, cannot influence carbon emissions disclosure.